Socioeconomic inequalities in underweight children: a cross-sectional analysis of trends in West Africa over two decades - Habila Adamou; Gregoire Naba; Hamidou Koné (BMJ Open, 2024)
Objective To study trends in socioeconomic inequalities in underweight children in West Africa, and specifically to analyse the concentration index of underweight inequalities and measure inequalities in the risk of being malnourished by household wealth index.Design Cross-sectional study.Setting The study used 50 Demographic and Health Surveys (DHS) and Multiple Indicator Cluster Surveys conducted between 1999 and 2020 across 14 countries by the DHS and UNICEF.Participants The study included 481 349 children under the age of 5 years.Primary and secondary outcome measures The analysis used three variables: weight-for-age index, household wealth index and household residence. The inequality concentration index for underweight children and the relative risk of being underweight between 2000 and 2020 were calculated.Results The prevalence of underweight in West Africa showed a downward trend from 2000 to 2020. Nonetheless, the prevalence of underweight children under 5 years of age is still very high in West Africa compared with other sub-Saharan African countries, and the sustainable development objective is yet to be achieved. There was a wide disparity among countries and significant socioeconomic inequalities in underweight children within countries. The proportions of underweight children were concentrated in poor households in all countries in West Africa and over all periods. Socioeconomic inequalities in underweight children were more significant in countries where the prevalence of underweight was low. These inequalities were more pronounced in urban areas in West Africa from 2000 to 2020.Conclusions and relevance There is a high concentration of socioeconomic inequalities in underweight children in disadvantaged households in West Africa.